2007
DOI: 10.1074/jbc.m609025200
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Mitochondrial Heat Shock Protein 70 Promotes Progeria-like Phenotypes in Caenorhabditis elegans

Abstract: Mitochondrial heat shock protein 70 (mthsp70) functions as a mitochondrial import motor and is essential in mitochondrial biogenesis and energy generation in eukaryotic cells. HSP-6 (hsp70F) is a nematode orthologue of mthsp70. Knockdown of HSP-6 by RNA interference in young adult nematodes caused a reduction in the levels of ATP-2, HSP-60 and CLK-1, leading to abnormal mitochondrial morphology and lower ATP levels. As a result, RNA interference-treated worms had lower motility, defects in oogenesis, earlier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 60 publications
(45 reference statements)
1
65
0
Order By: Relevance
“…Previous evidence suggested an elevated level of cellular ROS in HGPS cells (Kimura etĀ al ., 2007; Viteri etĀ al ., 2010; Riveraā€Torres etĀ al ., 2013; Villaā€Bellosta etĀ al ., 2013). To further analyze the functional defects in HGPS mitochondria, we measured both the mitochondrialā€specific superoxide (MitoSOX) and the intracellular ROS (DCFDA) and found both were significantly higher in progerinā€expressing fibroblast cells compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence suggested an elevated level of cellular ROS in HGPS cells (Kimura etĀ al ., 2007; Viteri etĀ al ., 2010; Riveraā€Torres etĀ al ., 2013; Villaā€Bellosta etĀ al ., 2013). To further analyze the functional defects in HGPS mitochondria, we measured both the mitochondrialā€specific superoxide (MitoSOX) and the intracellular ROS (DCFDA) and found both were significantly higher in progerinā€expressing fibroblast cells compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently found that expression of HSP70 suppresses UV-induced DNA damage and stimulates its repair process at the skin in mice (56). Other beneficial effects of HSP70, such as stimulation of wound-healing at the skin and anti-aging activity have also been suggested (57)(58)(59)(60). Furthermore, because recent reports suggest that MITF is an oncogene and its activation is involved in the progression of melanoma (61), the inhibitory effect of HSP70 on MITF would be beneficial for the prevention of UVinduced melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the biological aging process, studies of C. elegans and D. melanogaster have suggested that molecular chaperones directly control longevity. For example, Hsf1 knockdown in C. elegans reduces longevity and mtHsp70 knockdown promotes a progeria-like phenotype (22,26). In addition, numerous heat shock proteins (including Hsp16, mtHsp70, Hsp27, and Hsp70) have also been shown to be directly related to life span in C. elegans and D. melanogaster (44,47).…”
Section: Discussionmentioning
confidence: 99%